The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/tbj.13494
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis on safety and effectiveness of hypofractioned post‐mastectomy radiotherapy

Abstract: The data supporting hypofractionated post‐mastectomy radiotherapy is limited. The purpose of this study is to present the experience from Tarnów of hypofractionated PMRT over 20 fractions with respect to toxicity and effectiveness. We delivered post‐mastectomy radiotherapy at the dose of 45 Gy in 20 fractions to the chest wall and the draining regional lymph nodes. The primary outcome of interest was to ensure that the rate of grade 3 or greater toxicity from the hypofractionation, at any time point, was non‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Multiple retrospective studies support promising outcomes with HF-PMRT (Table 1) (32)(33)(34)(35)(36).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…Multiple retrospective studies support promising outcomes with HF-PMRT (Table 1) (32)(33)(34)(35)(36).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…Fibrosis increases over decades [137,138] and it requires both cosmetic correction in severe cases and psychological care [139]. RT-fibrosis also contributes to lymphedema, which results in impaired function and decreased quality of life [140]. There is inevitably some exposure of the lungs to irradiation during RT for breast cancer treatment, and lung fibrosis proceeds for up to 10 years [137,138].…”
Section: Lpa Signaling and Radiation Fibrosis Syndromementioning
confidence: 99%
“…There is growing interest in continuing study of hypofractionation after postmastectomy [10]. Emerging evidence has suggested that postmastectomy HFRT may be as effective as CFRT for patients at high risk of locoregional recurrence [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%